TREATMENT OF STRONG WASTEWATER FROM A PHARMACEUTICAL PLANT - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 1993)
Full-scale treatment of a strong wastewater which contained refractory organic chemicals and bioinhibitors from a pharmaceutical plant was outlined. In the treatment process, iron(II)-hydrogen peroxide system was used for the pretreatment of effluent prior to biological treatment. Overall 92-96% treatment yield was achieved with more economical advantages compared with the conventional treatment processes.
Keywords: Pharmaceutical wastewater; hydrogen peroxide; oxydation; iron(II)